HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN PERAWATAN DIRI PADA LANSIA DI PUSKESMAS KENTEN PALEMBANG TAHUN 2021 - Evi Royani; M. Ravi (Jurnal Kesehatan dan Pembangunan, 2022)
The World Health Organization (WHO) estimates that the number of elderly people in 2025 worldwide will reach 1.2 billion people which will continue to grow to 2 billion people in 2050. This increase in the number of elderly people will have an impact on various lives. The main impact of this increase in the elderly is an increase in the dependence of the elderly. The purpose of the study was to determine the relationship between family support and self-care for the elderly at Kenten Palembang Health Center in 2021. The research method used a cross sectional approach. The population in this study were all the elderly who visited the Kenten Health Center in Palembang when the research was conducted. The number of samples was 25 respondents using the accidental sampling method. The results showed that the frequency distribution of the elderly who did self-care independently was 16 respondents (64%), the frequency distribution of family support was mostly good as many as 14 respondents (56%). The results of the statistical test showed that there was a significant relationship between family support and self-care for the elderly at the Kenten Palembang Health Center in 2021 with a P value = 0.017. Suggestions are expected to be able to further complement references such as source books, health magazines, journals, and materials that support this research, especially those related to the relationship between family support and self-care for the elderly.